STUDENTS’ PERSPECTIVE TOWARD THE BENEFIT OF ALTISSIA IN LEARNING ENGLISH - Ivvon Septina Bella; Reza Novianda; Fajrinur Fajrinur (Sean Institute, 2022)
This research was a case study which aimed to investigate the students’ perspective and the benefits of using Altissia in learning English. The research was conducted at Universitas Islam Kebangsaan Indonesia and the subjects of the research were 10 students of Business Administration class E and 10 students of Accounting class B, and the data was collected through student interviews and questionnaires. This research found that most of the students have a good perspective on the benefits of using Altissia in learning English. They found the learning process more effective and interesting than usual. Students also showed an improvement in their English skills after using Altissia media, according to the results of a post-test conducted by the researchers. The results of the interviews were also supported by the results of a questionnaire that indicated that students felt that learning English by using Altissia was enjoyable and they were satisfied with the learning process and results.